KAPASITAS PENGELOLA PROGRAM PENYEDIAAN AIR MINUM DAN SANITASI BERBASIS MASYARAKAT (PAMSIMAS) DI DESA TANJUNG BALAM KECAMATAN SIAK HULU KABUPATEN KAMPAR - Lili Wulan Sari; Mimin Sundari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The increasing population growth causes the use of water to increase so that the need for water quality increases, the community-based drinking water supply and sanitation program is a national program that aims to increase community access to sustainable drinking water and sanitation services in rural and periurban areas (suburban areas). based on a community approach. In this case, the capacity of program managers at the community level is needed which is managed by the management agency for water supply and sanitation facilities so that the sustainability of the program in the village can be utilized by the community. The purpose of this study was to determine the capacity of the community-based water supply and sanitation program managers in the village of Tanjung Balam and to determine the factors inhibiting the capacity of the community-based water supply and sanitation program managers in the village of Tanjung Balam. This study used purposive sampling technique with qualitative research using a case study approach and the required data, both primary and secondary data, were obtained through observation, interviews and documentation and then analyzed based on the research problem. The results of this study indicate that: there is still a lack of capacity in managing community-based drinking water and sanitation programs in the village of Tanjung Balam because there are still complaints from the community about mossy water, sandy and there are still people who have not participated in the program. Inhibiting factors in measuring capacity in Tanjung Balam Village are incentives in the form of salaries, training and people's reluctance to participate.Keywords: Management capacity, program, sanitation, water quality